2022
DOI: 10.1155/2022/5299753
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Pulsed Radiofrequency Combined with Intravenous Lidocaine Infusion in the Treatment of Subacute Herpes Zoster Neuralgia

Abstract: Objective. Under the guidance of a digital subtraction angiography (DSA) machine, via fluoroscopic imaging techniques, patients diagnosed with herpes zoster neuralgia at the subacute stage, where self-reported pain lasts between 30 and 90 days, were treated with nerve pulsed radiofrequency surgery combined with intravenous lidocaine infusion or saline infusion as control. This study explores the clinical efficacy, safety, and clinical value of the combined treatment compared with nerve pulsed radiofrequency su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 40 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Fei et al 22 confirmed that PRF combined with paravertebral injection of recombinant human interferon‐α2b was an effective treatment for acute stage herpes zoster neuralgia. Zhang et al 23 reported that PRF combined with intravenous lidocaine infusion can effectively relieve pain, reduce the number of analgesic drugs used, and improve sleep and quality of life. In fact, the DRG is a key structure in PRF treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fei et al 22 confirmed that PRF combined with paravertebral injection of recombinant human interferon‐α2b was an effective treatment for acute stage herpes zoster neuralgia. Zhang et al 23 reported that PRF combined with intravenous lidocaine infusion can effectively relieve pain, reduce the number of analgesic drugs used, and improve sleep and quality of life. In fact, the DRG is a key structure in PRF treatment.…”
Section: Discussionmentioning
confidence: 99%